The Brazilian men’s artistic gymnastics in the international competitive panorama (1987-2008) - Oliveira, Mauricio Santos (2009)
The Brazilian Men's Artistic Gymnastics (MAG) have been suffering significant advances in the recent decades leaving the state of a meaningless country in the international arena to gain international recognition due the good results from our athletes. This article analyzed the performance of Brazilian gymnasts in the major competitions during the period of 1987-2008. The main objective of this study is to provide further understanding regarding the performance of Brazilian gymnasts in the MAG competitive panorama in recent years and also analyze the factors that had assisted in this development process. To setting-up the data, was held a bibliographic research through books, magazines, articles and websites specialized in this sport. As a result of the analysis, we could imply that the improvement in brazilian international competitive results were influenced by the increase of the financial support. This financial support resulted in better organization and infrastructure for training and competition.